Thalamic deep brain stimulation for neuropathic pain after amputation or brachial plexus avulsion. - Pereira, E; Boccard, S; Linhares, P; Chamadoira, C; Rosas, M; Abreu, P; Rebelo, V; Vaz, R; Aziz, T (2013)
OBJECT: Fifteen hundred patients have received deep brain stimulation (DBS) to treat neuropathic pain refractory to pharmacotherapy over the last half-century, but few during the last decade. Deep brain stimulation for neuropathic pain has shown variable outcomes and gained consensus approval in Europe but not the US. This study prospectively evaluated the efficacy at 1 year of DBS for phantom limb pain after amputation, and deafferentation pain after brachial plexus avulsion (BPA), in a single-center case series. METHODS: Patient-reported outcome measures were collated before and after surgery, using a visual analog scale (VAS) score, 36-Item Short-Form Health Survey (SF-36), Brief Pain Inventory (BPI), and University of Washington Neuropathic Pain Score (UWNPS). RESULTS: Twelve patients were treated over 29 months, receiving contralateral, ventroposterolateral sensory thalamic DBS. Five patients were amputees and 7 had BPAs, all from traumas. A postoperative trial of externalized DBS failed in 1 patient with BPA. Eleven patients proceeded to implantation and gained improvement in pain scores at 12 months. No surgical complications or stimulation side effects were noted. In the amputation group, after 12 months the mean VAS score improved by 90.0% ± 10.0% (p = 0.001), SF-36 by 57.5% ± 97.9% (p = 0.127), UWNPS by 80.4% ± 12.7% (p < 0.001), and BPI by 79.9% ± 14.7% (p < 0.001). In the BPA group, after 12 months the mean VAS score improved by 52.7% ± 30.2% (p < 0.001), SF-36 by 15.6% ± 30.5% (p = 1.000), UWNPS by 26.2% ± 40.8% (p = 0.399), and BPI by 38.4% ± 41.7% (p = 0.018). Mean DBS parameters were 2.5 V, 213 microseconds, and 25 Hz. CONCLUSIONS: Deep brain stimulation demonstrated efficacy at 1 year for chronic neuropathic pain after traumatic amputation and BPA. Clinical trials that retain patients in long-term follow-up are desirable to confirm findings from prospectively assessed case series.